2005
DOI: 10.1007/s10620-005-3059-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Antiviral Therapy on Asymptomatic Mixed Cryoglobulinemia in Naive Patients with Chronic Hepatitis C Virus Infection: A Preliminary Study

Abstract: The clinical spectrum of mixed cryoglobulinemia embraces several manifestations: recurrent vascular purpura, weakness, arthralgia/arthritis, glomerulonephritis, peripheral neuropathies, and Raynaud's phenomenon. Mixed cryoglobulinemia is currently treated with steroids, low-antigen content diet, immunosuppressors, plasma exchange, and antiviral therapy, namely, alpha -interferon alone or, more recently, in association with ribavirin. In the present research, we verified the effectiveness of combined therapy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…30,31 In addition, successful treatment of HCV infection with IFN/ribavirin, or elimination of B cells with novel anti-CD20 chimeric antibodies such as rituximab, leads to resolution of mixed cryoglobulinemia, regression of IgM overproduction and clearance of B-cell clones. [32][33][34][35][36] Our data clearly support a role for up-regulation of B-cell activation and immunoglobulin production in response to HCV core protein. We found that HCV core could bind gC1qR, a known receptor for HCV core that is expressed on CD20 + B cells.…”
Section: Discussionsupporting
confidence: 54%
“…30,31 In addition, successful treatment of HCV infection with IFN/ribavirin, or elimination of B cells with novel anti-CD20 chimeric antibodies such as rituximab, leads to resolution of mixed cryoglobulinemia, regression of IgM overproduction and clearance of B-cell clones. [32][33][34][35][36] Our data clearly support a role for up-regulation of B-cell activation and immunoglobulin production in response to HCV core protein. We found that HCV core could bind gC1qR, a known receptor for HCV core that is expressed on CD20 + B cells.…”
Section: Discussionsupporting
confidence: 54%
“…However, CGs can persist despite SVR [44,47], suggesting that viral clearance and sustained disappearance of CGs are not necessarily closely coupled. The failure to completely clear CGs despite SVR supports the hypothesis that antiviral treatment only partially interferes with the B-cell activities responsible for persistent RF and CGs [66]. Overall, complete immunologic response should not be assumed upon clearance of peripheral HCV, even in sustained responders.…”
Section: Immunologic Responsementioning
confidence: 62%
“…In a small case series of 25 patients, some patients achieved virologic clearance initially, but all had detectable HCV RNA at the end of therapy [11]. In another case series that included patients with asymptomatic MC, combination treatment with IFN and ribavirin was effective and led to permanent resolution of cryoglobulinemia; however, in rare cases, the disease initially can be detected distantly after successful treatment of HCV [12]. This argues against HCV being the only risk factor for MC in such patients.…”
Section: Mixed Cryoglobulinemiamentioning
confidence: 99%